Neuroticism is associated with higher antenatal care utilization in obstetric low‐risk women. (10th December 2018) - Axfors, Cathrine; Hellgren, Charlotte; Volgsten, Helena; Skoog Svanberg, Agneta; Ekselius, Lisa; Wikström, Anna‐Karin; Ramklint, Mia; Skalkidou, Alkistis; Sundström‐Poromaa, Inger
Abstract: Introduction: Elevated neuroticism is associated with higher health care utilization in the general population. This study aimed to investigate the association between neuroticism and the use of publicly financed antenatal care in obstetric low‐risk women, taking predisposing and need factors for health care utilization into consideration. Material and methods: Participants comprised 1052 obstetric low‐risk women (no chronic diseases or adverse pregnancy conditions) included in several obstetrics/gynecology studies in Uppsala, Sweden. Neuroticism was self‐rated on the Swedish universities Scales of Personality. Medical records of their first subsequent pregnancy were scanned for antenatal care use. Associations between antenatal care use and neuroticism were analyzed with logistic regression (binary outcomes) or negative binomial regression (count outcomes) comparing the 75th and 25th neuroticism percentiles. Depending on the Akaike information criterion the exposure was modeled as either linear or with restricted cubic splines. Analyses were adjusted for predisposing (sociodemographic and parity) and need factors (body mass index and psychiatric morbidity). Results: After adjustment, women with higher neuroticism had more fetal ultrasounds (incidence rate ratio = 1.09, 95% confidence interval (CI) 1.02‐1.16), more emergency visits to an obstetrician/gynecologist (incidence rate ratio = 1.22, 95% CI 1.03‐1.45) and were more likely to visit a fear‐of‐childbirth clinic (odds ratio = 2.71, 95% CI 1.71‐4.29). Moreover, they more often consulted midwives in specialized antenatal care facilities (significant J‐shaped association). Conclusions: Neuroticism was associated with higher utilization of publicly financed antenatal care in obstetric low‐risk women, even after adjusting for predisposing and need factors. Future studies should address the benefits of interventions as a complement to routine antenatal care programs to reduce subclinical anxiety.